ICT ADOPTION AMONG REAL ESTATE AGENTS IN MALAYSIA - Mohamad, Murni; Mohd Aini, Ainoriza; Alias, Anuar (International Journal of Property Sciences (E-ISSN: 2229-8568), 2024)
The success of real estate agents relies on the ability to provide better services to their clients efficiently and seamlessly. The use of Information and Communication Technology (ICT) is benefiting real estate agents by making it more convenient for real estate agents to find clients, advertise the property, and facilitate the property transaction process, which is indubitable. Therefore, the main objective of this study is to assess the level of ICT usage by real estate agents in valuation and agency firms in Klang Valley, Malaysia. Data were gathered through a survey conducted with these firms, and 400 responses were collected using a quantitative study and analysed using descriptive statistics and the Relative Importance Index (RII) ranking. The study revealed that most respondents adopt ICT in their practices, with the most frequently used tools being Mobile Instant Messaging, Social Media, and Real Estate Agent Websites. However, technologies such as Virtual Reality, Augmented Reality, Robotic Process Automation, and Metaverse Real Estate are rarely utilised. The study concluded that the widespread application of ICT in real estate is evident. However, inadequate training, higher cost of acquisition, and shortage of skilled people are the barriers that limit its full potential within the sector. This study recommends that the top management of valuation and agency firms provide training programs and ongoing support that cater to the specific needs of real estate agents.